2013
DOI: 10.1073/pnas.1303966110
|View full text |Cite
|
Sign up to set email alerts
|

Two-state dynamics of the SH3–SH2 tandem of Abl kinase and the allosteric role of the N-cap

Abstract: The regulation and localization of signaling enzymes is often mediated by accessory modular domains, which frequently function in tandems. The ability of these tandems to adopt multiple conformations is as important for proper regulation as the individual domain specificity. A paradigmatic example is Abl, a ubiquitous tyrosine kinase of significant pharmacological interest. SH3 and SH2 domains inhibit Abl by assembling onto the catalytic domain, allosterically clamping it in an inactive state. We investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 53 publications
4
55
0
Order By: Relevance
“…The connector SH2-KD plays a central role in Abl regulation as has been highlighted by a number of previous reports 7,26,35,36 . The S140R/I substitution in particular causes a pronounced increase in Abl activity and shows increased resistance to the KD inhibitor imatinib 7,13 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The connector SH2-KD plays a central role in Abl regulation as has been highlighted by a number of previous reports 7,26,35,36 . The S140R/I substitution in particular causes a pronounced increase in Abl activity and shows increased resistance to the KD inhibitor imatinib 7,13 .…”
Section: Resultsmentioning
confidence: 91%
“…Abl, like many other kinases, is known to function as a graded rather than simply an “on” and “off” switch 19,20 . Given the dynamic nature of protein kinases 2123 insight into their conformational and energetic landscape 2426 is required to fully understand the underlying mechanisms of regulation and how kinases respond to diverse signals.…”
Section: Introductionmentioning
confidence: 99%
“…Microsecond all-atom simulations and differential scanning calorimetry have investigated the dynamics of the SH3-SH2 tandem that operates as a two-state switch, alternating between conformations observed in the autoinhibited and active complexes 63 . The biophysical, biochemical and computational studies of Abl and Src regulation have indicated a complex interplay between the SH3 and SH2 domains, the SH2 linker and the catalytic domain.…”
Section: Introductionmentioning
confidence: 99%
“…Computational approaches have studied the atomic details of the protein kinase dynamics and regulation at different levels of complexity : from detailed analyses of the catalytic domain and drug resistance [51][52][53][54][55][56][57][58][59] to simulations of the regulatory assemblies [60][61][62][63][64] . In our previous studies, we analyzed mechanisms of allosteric kinase regulation by integrating multiscale simulations and modeling of long-range communications 60,61 .…”
Section: Introductionmentioning
confidence: 99%
“…Many longer simulations focus on the alteration of key structural features (e.g., salt bridges, domain or feature orientation and drug binding) and how these affect the free energy landscape of the protein [62][63][64][65]. These types of studies have provided information on the progression of these proteins into more active conformations following disease causing mutations [64,66] as well as critical information on the effect of mutations on drug resistance [65,66].…”
Section: From Numbers To Predictions: In Silico Analysis Of Mutationsmentioning
confidence: 99%